Tracking Legal Basis Through Takhrij Hadis Digital Software (Case Study of the Bahtsul Masail Forum Komunikasi Ta'mir Masjid and Musholla Duwet - Wates - Kediri) - Imam Masrur; Khamim Khamim; Duwi Hariono (IAIN Ponorogo, 2021)
Since the beginning of its appearance at the Prophet's time to the Companions, the Hadith has never been free from controversy. For example, the delay in codification and the prohibition on hadith writing. This condition made orientalists accused the Hadith is inauthentic. Another issue is the issue of authority, whether Hadith has the legal force that binds all people. Moreover, if the Hadith deals with various interests, its authoritative power becomes conditional. It can be very authoritative when dealing with an ongoing problem in a particular area but barren when dealing with the same problem in another place. In Muslim society, the Hadith is the second authoritative source of law after the Qur'an. Even for the Hadith with mutawatir status, the power of authority is the same as the Qur'an. The digitization of the Hadith is still very weak and limited when compared to the Qur'an, so it is difficult to find its software. People who do not have competence in the Hadith will choose to use search engines on the internet such as Google. The results obtained also come from sources whose credibility is dubious. Lidwa Pusaka answered this challenge by releasing the Nine Imams Book of Hadith software. The position and function of the Hadith are very vital as a guide for the life of Muslims. When solving a problem without using Hadith, accusations of anti-hadith, breaking the Sunnah, and various negative stigmas will arise.